Analysis of prevalence of selected risk factors for cancer in a selected population and sociodemographic variables - Smoleń, Ewa; Cipora, Elżbieta; Jarema, Magdalena; Hombek, Karolina (Journal of Education, Health and Sport, 2017)
Indtroduction. Important risk factors for cancer include smoking, alcohol consumption and exposure to ultraviolet rays. Their avoidance reduces the risk of cancer. Aim. Defining risk factors for cancer among residents of Sanok district. Material and methods. The study included 157 residents of Sanok district in 2015. The method of diagnostic survey, engineering survey was used, whereas a research tool was the original questionnaire. In the assessment of dependence a statistical significance level of p <0.05 was used. Results. Smoking was more often declared by male patients from 31 to 50 years of age, with vocational education. The largest percentage of respondents smoked about 10 cigarettes a day. Most often the respondents reported smoking cigarettes for a period of two years. Sunbathing was most commonly taken by respondents below 30 years of age and with secondary education. Exposing to the sunlight was often indicated by patients, villagers, and younger people. Protective creams were applied more often by people who were not hospitalized, respondents under 30 years of age, with higher education, and women. Conclusions. Existing unhealthy behaviors represent modifiable risk factors for cancer, which makes it possible to plan and take action in the test environment, aiming to eliminate them.